SANGGAH KAMULAN DADAP SAKTI di DESA LES KECAMATAN TEJAKULA KABUPATEN BULELENG KAJIAN FILSAFAT HINDU - Ni Kadek Adnyani; I Wayan Gata; Ayu Veronika Somawati (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2023)
Hinduism is a religion that also teaches worship of God and its manifestations by using a form or symbol whose existence is purified. A holy place is a place for Hindus to carry out daily worship or on certain days. There are 2 (two) Sanggah Kamulan Dadap Sakti in Les Village. Namely the Sanggah Kamulan Dadap Sakti Surya and the Sanggah Kamulan Dadap Sakti Taksu. Sanggah Kamulan Surya is a place to worship Bhatara Hyang Guru. Community belief in Les Village in worshiping Sanggah Kamulan Dadap Sakti has the belief that what is worshiped in Sanggah Kamulan Dadap Sakti is Ida Sang Hyang Widhi Wasa/God and its manifestations, Tri Purusa, Purusa-Pradana, Bapanta-Ibunta, and Atmanta. Between the two Sanggah Kamulan Dadap Sakti a stone is placed, or there is also someone who places a stone under the Sanggah Kamulan Dadap Sakti which is called Ratu Gede Dasar. This study uses symbol theory, religious theory, and meaning theory. The research method used is descriptive qualitative method. This study examines the form of the Sanggah Kamulan Dadap Sakti, the function of the Sanggah Kamulan Dadap Sakti and the Meaning of the Sanggah Kamulan Dadap Sakti. The results of this study include; (1) the form of Sanggah Kamulan Dadap Sakti, namely Sanggah Kamulan Dadap Sakti in Les Village has a height of 1 m, a length of 1.5 m, and a width of 1 m. (2) The functions of Sanggah Kamulan Dadap Sakti in Les Village consist of: religious function, educational function, togetherness function, ethical function, aesthetic function, function of preserving Hindu religion, function of giving a sense of closeness, and function of providing a sense of security. (3) The meaning of Sanggah Kamulan Dadap Sakti in Les Village consists of: The meaning of Hindu religious education, the meaning of purification, and the meaning of harmony.